Renal targeting: peptide-based drug delivery to proximal tubule cells - Wischnjow, Artjom; Sarko, Dikran; Janzer, Maria; Kaufman, Christina; Beijer, Barbro; Brings, Sebastian; Haberkorn, Uwe; Mier, Walter (Bioconjugate chemistry, 2016)
Kidney-specific drug targeting is an attractive strategy to reduce unwanted side effects and to enhance drug efficacy within the renal tissue. For this purpose a novel kidney-specific drug carrier was developed. The peptide sequence (KKEEE)3K triggers exceptional renal specificity at high accumulation rates. Micro-PET imaging studies of megalin-deficient mice indicate that the cellular endocytosis of this carrier is mediated by megalin. This assumption is supported by immunohistochemical analysis of FITC-labeled carrier peptide, which exclusively accumulated at the apical side of proximal tubule cells within the renal cortex. Scintigraphic studies of modified ciprofloxacin conjugated to (KKEEE)3K confirmed the excellent drug targeting potential of the peptide carrier. The conjugate accumulated entirely in the kidneys, revealing flawless redirection of ciprofloxacin, a compound that is mainly excreted by the liver. In conclusion, these results suggest the potential of (KKEEE)3K as a promising candidate for kidney-targeted drug delivery to proximal tubule cells.
Gesehen am 25.11.2019